The first late cretaceous mawsoniid coelacanth (Sarcopterygii: Actinistia) from North America: Evidence of a lineage of extinct 'living fossils'. - Lionel Cavin (Public Library of Science (PLoS), 2021)
Today, the only living genus of coelacanth, Latimeria is represented by two species along the eastern coast of Africa and in Indonesia. This sarcopterygian fish is nicknamed a "living fossil", in particular because of its slow evolution. The large geographical distribution of Latimeria may be a reason for the great resilience to extinction of this lineage, but the lack of fossil records for this genus prevents us from testing this hypothesis. Here we describe isolated bones (right angular, incomplete basisphenoid, fragments of parasphenoid and pterygoid) found in the Cenomanian Woodbine Formation in northeast Texas that are referred to the mawsoniid coelacanth Mawsonia sp. In order to assess the impact of this discovery on the alleged characteristic of "living fossils" in general and of coelacanths in particular: 1) we compared the average time duration of genera of ray-finned fish and coelacanth in the fossil record; 2) we compared the biogeographic signal from Mawsonia with the signal from the rest of the vertebrate assemblage of the Woodbine formation; and 3) we compared these life traits with those of Latimeria. The stratigraphical range of Mawsonia is at least 50 million years. Since Mawsonia was a fresh, brackish water fish with probably a low ability to cross large sea barriers and because most of the continental components of the Woodbine Fm vertebrate assemblage exhibit Laurasian affinities, it is proposed that the Mawsonia's occurrence in North America is more likely the result of a vicariant event linked to the break-up of Pangea rather than the result of a dispersal from Gondwana. The link between a wide geographic distribution and the resilience to extinction demonstrated here for Mawsonia is a clue that a similar situation existed for Latimeria, which allowed this genus to live for tens of millions of years.